REDUCTIVE-SULFURIZING SMELTING TREATMENT OF SMELTER SLAG FOR COPPER AND COBALT RECOVERY - Li, Yun; Yang, Shenghai; Tang, Chaobo; Chen, Yongming; He, Jing; Tang, Motang (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
Recovery of copper and cobalt from smelter slag using reductive-sulfurizing smelting method was performed in this study. The effects of reductive agent (coke), sulfurizing agent (pyrite), slag modifier (CaO) and smelting temperature and duration on the extractive efficiencies of Cu, Co and Fe were discussed. The phase compositions and microstructure of the materials, copper-cobalt matte and cleaned slag were determined. The results showed that copper and cobalt contents in cleaned slag could decrease averagely to 0.18% and 0.071% respectively after cleaning. 91.99% Cu and 92.94% Co and less than 38.73% Fe were recovered from the smelter slag under the optimum conditions: 6 wt.% coke, 20 wt.% pyrite and 6 wt.% CaO addition to the smelter slag, smelting temperature of 1350°C and smelting duration of 3h. The addition of CaO can increase the selectivity of Co recovery. The cleaning products were characterized by XRD and SEM-EDS analysis. The results showed that the main phases of copper-cobalt matte were iron sulfide (FeS), geerite (Cu8S5), iron cobalt sulfide (Fe0.92Co0.08S) and Fe-Cu-Co alloy. The cleaned slag mainly comprised fayalite (Fe2SiO4), hedenbergite (CaFe(Si2O6)) and magnetite (Fe3O4).